Cultivating an ethos: collegial co-discovery in a Children and Youth University. Issue 1 (2nd January 2020) - Beier, J. Marshall; Raha, Sandeep
ABSTRACT: Since 2011, the McMaster Children and Youth University has offered free monthly lectures on the campus of McMaster University. Though aimed at children and youth aged seven to fourteen, there are no formal age restrictions and events regularly see attendance by young people beyond both thresholds of this age range. A central aim and guiding principle of the program has been to promote and support participants' discovery of themselves as acting subjects in knowledge practices, including the production of new knowledge. Placing our model of the children's university in comparative perspective with programs in Europe and Hawaii that share important aspects of this vision, we elaborate the bases of an ethos of collegial co-discovery urging young participants to question, discover, and create. The university setting presents particular challenges that call for careful attention to conventional practices and commitments and the sorts of relationships they variously enable or foreclose. Taking young people seriously as bona fide bearers and producers of knowledge relies to a significant extent on our ability to embrace a strengths-based view of childhood and to confront relations of power predisposed toward authorizing some voices to the exclusion of others.